Cooperation performance of multi-organisations operating in a sharing economy: game theory with agent-based modelling. Issue 22 (16th November 2020) - Meng, Qingfeng; Chu, Leilei; Li, Zhen; Chen, Jingxian; Du, Jianguo; Wu, Changzhi
Abstract : Sustainable development within a sharing economy requires close cooperation between participating organisations, while a more complicated management problem involves how to improve the cooperation performance between such organisations. This paper researches multi-organisational cooperation under a shared economy model to analyse the impact of the organisation's revenue distribution plan, the organisational members' characteristic abilities and other factors on the cooperation performance among organisations and core enterprises' profit performance. It aims to provide a theoretical basis for core enterprises to rationally formulate revenue distribution strategy and the promotion of sustainable development of the shared economy. The research results reveal that under the shared economy model, the core enterprise's revenue-distribution method based on fixed revenue and revenue-sharing can improve cooperation performance among organisational members to some extent. Moreover, the barriers and obstacles in organisations' cooperation process are small, which will positively increase system profits, core enterprise profit and the proportion of core enterprise profits, but does not necessarily improve system profit margins. The core enterprise should control the cooperation costs between organisations through different incentive strategies to achieve better system profits and system profit margins.